The Role of IL-10 in Malaria: A Double Edged Sword - Kumar, Rajiv; Ng, Susanna; Engwerda, Christian (Frontiers in Immunology, 2019)
IL-10 produced by CD4+ T cells suppresses inflammation by inhibiting T cell functions and the upstream activities of antigen presenting cells (APCs). IL-10 was first identified in Th2 cells, but has since been described in IFNγ-producing Tbet+ Th1, FoxP3+ CD4+ regulatory T (Treg) and IL-17-producing CD4+ T (Th17) cells, as well as many innate and innate-like immune cell populations. IL-10 production by Th1 cells has emerged as an important mechanism to dampen inflammation in the face of intractable infection, including in African children with malaria. However, although these type I regulatory T (Tr1) cells protect tissue from inflammation, they may also promote disease by suppressing Th1 cell-mediated immunity, thereby allowing infection to persist. IL-10 produced by other immune cells during malaria can also influence disease outcome, but the full impact of this IL-10 production is still unclear. Together, the actions of this potent anti-inflammatory cytokine along with other immunoregulatory mechanisms that emerge following Plasmodium infection represent a potential hurdle for the development of immunity against malaria, whether naturally acquired or vaccine-induced. Recent advances in understanding how IL-10 production is initiated and regulated have revealed new opportunities for manipulating IL-10 for therapeutic advantage. In this review, we will summarise our current knowledge about IL-10 production during malaria and discuss its impact on disease outcome. We will highlight recent advances in our understanding about how IL-10 production by specific immune cell subsets is regulated and consider how this knowledge may be used in drug delivery and vaccination strategies to help eliminate malaria.